Association of vasopressors with mortality in critically ill patients with COVID-19: a systematic review and meta-analysis - Mermiri, Maria; Mavrovounis, Georgios; Laou, Eleni; Papagiannakis, Nikolaos; Pantazopoulos, Ioannis; Chalkias, Athanasios (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2023)
Exogenous catecholamines may have pronounced side effects and affect physiological cascades. The aim of this study was to investigate the effect of vasopressors on mortality of critically ill patients with coronavirus disease 2019 (COVID-19). A systematic search of PubMed, Scopus, and ClinicalTrials.gov was conducted for relevant articles until December 2022. Eligibility criteria were randomized controlled and non-randomized trials. The primary outcome was in-hospital and 30-day mortality. The quality of studies was assessed using the Methodological Index for Non-Randomized Studies (MINORS) tool, while paired meta-analysis was used to estimate the pooled risk ratios (RR) along with their 95% Confidence Interval (95% CI). Analyses of 22 studies ( n = 8034) revealed that vasopressor use is associated with mortality compared to no vasopressor therapy [RR (95%CI): 4.30 (3.21, 5.75); p < 0.001]. In-hospital and 30-day mortality are significantly higher in patients who receive vasopressors [RR (95%CI): 4.60 (2.47, 8.55); p < 0.001 and RR (95%CI): 2.97 (1.72, 5.14); p < 0.001, respectively]. Also, analyses of data from 10 studies ( n = 3519) revealed that vasopressor use is associated with acute kidney injury [RR (95%CI): 3.17 (2.21, 4.54); p < 0.001]. In conclusion, current use of vasopressors in critically ill patients with COVID-19 may be associated with higher in-hospital mortality, 30-day mortality, and incidence rate of acute kidney injury. Further research is required to estimate the correlation of specific vasopressor characteristics (type, timing, dose, combination) with adverse effects and mortality in this population. Graphical Abstract